Risk Inequality in Tidal Flood Disasters on the Northern Coast of Java - Istriyani, Ratna (Journal of Contemporary Sociological Issues, 2025)
Indonesia's maritime potential contributes to economic benefits, particularly the coastal area of the Northern Coast of Java, which serves as a major maritim trade route. This has led to increased industrial activity through the development of industrial infrastructure, property, and public facilities. However, industrialization in the Northern Coast of Java has resulted in increased land subsidence, resulting in significant tidal flood over the past few years. This flooding has had a serious impact on the community and indicates class-based risk inequality. Therefore, this study uses Ulrich Beck's analytical framework on risk communities. The method used in this study are literature review and secondary data analysis obtained from previous researchs, articles or video of credible digital media, and data from relevant ministries. The research results indicate that tidal flood on the Northern Coast of Java is a natural disaster caused by tides and alluvial soil characteristics. However, the significance of tidal flood in recent years has been influenced by massive industrial activity as a manifestation of modernity, especially groundwater exploitation, which has accelerated land subsidence. The impact of tidal flood has become increasingly intense and extends to inland, impacting the ecological, economic, and social aspects of the community. However, the impacts of tidal flood are not evenly distributed, but rather accumulate among the directly affected communities, namely the lower classes, who have to bear the risks, because of no another choices.